In vitro susceptibility of Aspergillus and Fusarium associated with equine keratitis to new antifungal drugs. (16th May 2020) - Roberts, Darby; Cotter, Henry Van T.; Cubeta, Marc; Gilger, Brian C.
Abstract: Objective: To determine minimum inhibitory concentrations (MICs) of four fungal species isolated from horses presented with equine fungal keratitis (EFK) in the southeastern United States to previously untested azole, echinocandin, and carboxamide antifungal drugs. Methods: In vitro assays were performed to determine the susceptibility of Aspergillus flavus, A. fumigatus, Fusarium falciforme, and F. keratoplasticum to five antifungal drugs representing three modes of action. Results: Luliconazole exhibited increased growth inhibition against both Aspergillus and Fusarium compared to commonly used, standard antifungal drugs. MIC values for luliconazole at 0.001‐0.002 µg/mL were at least 25‐fold lower than all other antifungal drugs tested, including voriconazole. Conclusions: The increased antifungal activity of luliconazole observed in this study warrants further investigation for its potential as an antifungal drug for equine fungal keratitis.